Biochemical characterization of Fsa16295Glu from “Fervidibacter sacchari,” the first hyperthermophilic GH50 with β-1,3-endoglucanase activity and founding member of the subfamily GH50_3 - Covington, Jonathan K.; Torosian, Nicole; Cook, Allison M.; Palmer, Marike; Bryan, Scott G.; Nou, Nancy O.; Mewalal, Ritesh; Harmon-Smith, Miranda; Blaby, Ian K.; Cheng, Jan-Fang; Hess, Matthias; Brumm, Phillip J.; et al. (Frontiers in Microbiology, 2024)
The aerobic hyperthermophile "Fervidibacter sacchari" catabolizes diverse polysaccharides and is the only cultivated member of the class "Fervidibacteria" within the phylum Armatimonadota. It encodes 118 putative glycoside hydrolases (GHs), including two from GH family 50 (GH50). Here, we expressed, purified, and functionally characterized one of these GH50 enzymes, Fsa16295Glu. We show that Fsa16295Glu is a β-1,3-endoglucanase with optimal activity on carboxymethyl curdlan (CMcurdlan) and only weak agarase activity despite most GH50 enzymes being described as β-agarases.The purified enzyme has a wide temperature range of 4-95 °C (optimal 80 °C), making it the first characterized hyperthermophilic representative of GH50. The enzyme is also active at a broad pH range of at least 5.5-11 (optimal 6.5-10). Fsa16295Glu possesses a relatively high kcat/KM of 1.82 x 10 7 s -1 M -1 with CM-curdlan and degrades CM-curdlan nearly completely to sugar monomers, indicating preferential hydrolysis of glucans containing β-1,3 linkages. Finally, a phylogenetic analysis of Fsa16295Glu and all other GH50 enzymes revealed that Fsa16295Glu is distant from other characterized enzymes but phylogenetically related to enzymes from thermophilic archaea that were likely acquired horizontally from "Fervidibacteria". Given its functional and phylogenetic novelty, we propose that Fsa16295Glu represents a new enzyme subfamily, GH50_3.